RANCANG BANGUN SISTEM MONITOR KONDISI AIR DAN PAKAN BERBASIS IOT DENGAN CATU DAYA PLTS PADA KOLAM LELE - I Komang Alit Astawa; Putu Ananta Sastra Wijaya; I Made Aditya Wirawan; IGAP Raka Agung; I N Setiawan; I W Shandyasa; Pratolo Rahardjo; Yoga Divayana (Jurnal SPEKTRUM, 2025)
Catfish farming requires proper monitoring of pond water quality and feed management. Limited time for farmers to monitor ponds directly poses challenges in maintaining water quality and feeding schedule accuracy. This study aims to implement a water quality monitoring device using sensors and an automated scheduled feeding system. This research uses a system development method based on the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed device consists of sensors and actuators. Sensor data is displayed through the Firebase platform and OLED screen on the panel box. The system uses a 120 Wp solar panel with a LiFePO4 12V 22Ah battery as a power source. Testing for 3 days (May 18-20, 2025) showed an average pond water temperature of 25.1°C using DS18B20 sensor, average pH value of 7.7 using pH-4502c sensor, feed volume decreased from 6 kg to 4.9 kg (from 100% to 83%) measured using HC-SR04 sensor, and battery voltage between 13.2-13.8V measured using INA219 sensor. Automated feeding is carried out using a combination of a DC motor and servo motor. The results indicate that the system successfully integrates water quality monitoring and scheduled automated feeding using the Firebase platform. This system has the potential to be applied by fish farmers to overcome time constraints in direct pond monitoring.